(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2006)
Items on waste generation in the Riga city are analysed. Short presentation of the study methods is provided, and achieved results are presented. Three different dwelling areas have been investigated: multi-apartment houses with and without of waste shoots and private houses. Comparison of obtained results with similar ones have been got abroad is included. It is stated that average solid household waste generation in the Riga city is 199.2 kg / capita / year or 1.52 m3/ capita / year. Morphological composition of waste is analysed, and it is stated that following types of waste are dominating: putrescible waste, paper-cardboard, glass and plastics. Conclusion is done that generated waste amount strongly depends on value of the gross domestic product is done, i.e. increase of waste amount generated per capita maybe expected in the Riga city.